Trade Openness and Green Total Factor Productivity in China: The Role of ICT-Based Digital Trade - Zhang, Huan (Frontiers in Environmental Science, 2021)
The vigorous development of modern information and communication technology (ICT) has driven the digital trade featured by ICT technique and industry as the carrier. This paper empirically tests the impact of ICT-based digital trade openness on green total factor productivity (GTFP) by selecting ICT as the representative digital trade data of 30 provinces in China over the timespan 2002-2018. We employ slack-based model and Global Malmquist Luenberger (SBM-GML) estimation method to calculate the provincial GTFP, and explore the heterogeneous impact of digital trade openness on GTFP through scale effect, technology effect and structure effect. In terms of the empirical results, the panel fixed model and panel quantile estimation model both suggest the same findings. With the continuous expansion of the scale of digital trade, its scale effect has a significant inhibitory effect on GTFP, whereas the structure effect combined with human capital and the technology effect correlated with technological research and development (R&D) have a significant promoting effect on GTFP. The panel quantile regression model reveals that the interaction intensity increases gradually from low quantile to high quantile. Further robustness tests also verify the consistency and stability of the results. Finally, the paper puts forward corresponding practical suggestions for the construction of high-quality open pattern of digital trade and the coordinated development of GTFP. The specific policy implications including: (1) Emphasize on the penetration and connection effect of the new generation of ICT, and strengthen the construction of enterprise informatization. (2) Expand digital trade openness and broaden the field of industrial cooperation. (3) Optimize the industrial structure of digital trade and accelerate the development of core industries of digital trade. (4) Gradually promote the transformation of digital trade from relying on quantity and scale to product quality.